Synthesis and diagnosis of a number of new super oxo compounds derived from Schiff base complexes for dual cobalt - Saad El Mokhtar; Tamador Mahmoud; Lana Rashid (College of Education for Pure Sciences, 2013)
ABSTRACT:          The work included the preparation of cobalt complexes having general formula [ CoL] , where L is divalent tetradentate Schiff base ligand derived from benzyl and anthranilic acid or o-aminophenol with 1:2 molar ratio . These complexes reacted with H2O2 in the absence and in the presence of B (B= py , -pic , Pph3) at room temperature to obtain [ CoLO2 ] and [CoLBO2 ] complexes. All the prepared complexes were characterized by metal content analysis , molar conductance , spectral studies including I.R and electronic spectra as well as magnetic measurements. These studies revealed that all the complexes are non-electrolytes. The Schiff base ligands act as dibasic tetradentate ( NNOO-donor) , CoL complexes are square planar containing one unpaired electron. The electronic spectra reveals the oxidation of Co(II) to Co(III) in [CoLO2] and  [CoLBO2] complexes. These complexes show μeff values  related to one unpaired electron , that belongs to O2 mioety , which is supported by (υo-o) band in I.R spectra that related to O2 mioety. Hence superoxo compounds are realy recognized.